Can mud deposits indicate inundation extent of paleotsunamis? Insights from sediment-transport simulations for sand and mud - Watanabe, Masashi (2023)
Field surveys following the 2011 Tohoku-oki tsunami showed that mud tsunami deposits reached close to the tsunami inundation limit. However, the factors controlling the distribution of mud tsunami deposits remained unclear. We investigated these influencing factors by numerically simulating sand and mud transport after validating the tsunami inundation and distributions of sand and mud deposits during the 2011 Tohoku-oki tsunami based on our sensitivity analysis of parameters used in the mud and sand sediment simulations. We have revealed that when the source of mud sediments is only on the seafloor (i.e., no terrestrial source), mud is deposited along less than 10% of the inundation distance. In contrast, if a terrestrial source of mud is present, mud deposits can cover 100% of the inundation distance. We have also revealed that mud sediments are not formed when topographic slopes are steep (1/20–1/500), irrespective of a terrestrial mud source, because flow stagnation does not occur. Therefore, to reproduce past inundation ranges of tsunamis from the distribution of mud deposits, two conditions are required: (a) regions with onshore mud sediments and (b) a gentle topographic slope (around 1/1,000) to allow for long-time (more than 100 min) flow stagnation.